1998
DOI: 10.1074/jbc.273.38.24309
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositides Bind to Plasma Membrane CD14 and Can Prevent Monocyte Activation by Bacterial Lipopolysaccharide

Abstract: Although bacterial lipopolysaccharides (LPS) and several other microbial agonists can bind to mCD14 (membrane CD14), a cell-surface receptor found principally on monocytes and neutrophils, host-derived mCD14 ligands are poorly defined. We report here that phosphatidylinositol (PtdIns), phosphatidylinositol-4-phosphate, and other phosphatidylinositides can bind to mCD14. Phosphatidylserine (PS), another anionic glycerophospholipid, binds to mCD14 with lower apparent affinity than does PtdIns. LPS-binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 34 publications
3
64
0
Order By: Relevance
“…Previous studies have provided evidence that the antagonism of LPS activation through LBP/CD14/MD2/TLR4 is dependent upon the molecular class and species of phospholipid used as an antagonist (17)(18)(19)(20). We examined the molecular specificity of the POPG effect on RSV-elicited cytokine production by comparing the effects of POPG with a phospholipid counterpart containing a choline polar moiety, palmitoyl-oleoylphosphatidylcholine (POPC).…”
Section: Popg Specifically Attenuates Proinflammatory Cytokine Producmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided evidence that the antagonism of LPS activation through LBP/CD14/MD2/TLR4 is dependent upon the molecular class and species of phospholipid used as an antagonist (17)(18)(19)(20). We examined the molecular specificity of the POPG effect on RSV-elicited cytokine production by comparing the effects of POPG with a phospholipid counterpart containing a choline polar moiety, palmitoyl-oleoylphosphatidylcholine (POPC).…”
Section: Popg Specifically Attenuates Proinflammatory Cytokine Producmentioning
confidence: 99%
“…Additional studies have identified phosphatidylglycerol (PG) as an antagonist of LPS binding protein (LBP), and CD14 (18)(19)(20). Although PG constitutes about 10% of surfactant phospholipids, the high concentration of lipid in the extracellular surfactant layer within the alveolus, results in PG levels as high as 3.5 mg/mL This extraordinary level of PG is not found in any other tissue or mucosal surface in mammals.…”
mentioning
confidence: 99%
“…But the multifunctionality of CD14 is underscored by its role in apoptotic cell clearance when it induces an opposite macrophage response (Devitt et al 1998, Gregory 2000. In spite of binding to phospholipids, including PS (Wang et al 1998), it seems unlikely that CD14 can function as a PS receptor, at least when judged by in vitro assays of the engulfment ability of inactivated macrophages (Devitt et al 2003). By contrast, a putative candidate for CD14 recognition on apoptotic cell surface is the highly glycosylated Ig-superfamily member, the Intercellular adhesion molecule 3 (ICAM-3), constitutively expressed on leukocytes (Fawcett et al 1992).…”
Section: Apoptotic Cell Recognition In Mammalian Systems: Redundancymentioning
confidence: 99%
“…Work from our laboratory 8,10,24 and elsewhere 25 has shown that human and murine macrophages utilise plasma membrane-anchored CD14 (mCD14) in apoptotic-cell clearance. In view of CD14's established capacity to interact with phospholipids, [26][27][28][29] we reasoned that CD14 might function as a PS-receptor for apoptotic cells. 10 We now report, however, that CD14 does not function preferentially as a PS-receptor in apoptotic-cell clearance, supporting the PS-R's principal role in this regard.…”
Section: Introductionmentioning
confidence: 99%